Association between MAFB rs17820943 and rs6072081 polymorphism and risk of nonsyndromic cleft lip with or without cleft palate: a meta-analysis. Issue 9 (November 2020) - Liang, X.; Huang, L.; Ou, Y.; He, Y.; Tang, S.
Abstract: While there have been previous studies examining the relation between the rs17820943 and rs6072081 polymorphisms in the v-maf musculoaponeurotic fibrosarcoma oncogene homolog B (MAFB) gene and rates of nonsyndromic cleft lip with or without cleft palate (NSCL/P), at present the results of these studies have been inconsistent. This meta-analysis therefore aimed to conduct a more robust assessment of the association between the MAFB rs17820943 and rs6072081 polymorphisms and NSCL/P risk. The Embase, Web of Science, PubMed, the China National Knowledge Internet (CNKI), and Wanfang databases were systematically searched to identify relevant studies. In total, five studies incorporating 2769 patients and 2885 controls were identified assessing the rs17820943 polymorphism and three studies incorporating 1242 patients and 1310 controls assessing the rs6072081 polymorphism were identified. This analysis revealed the MAFB rs17820943 and rs6072081 polymorphisms to be linked to a significantly reduced NSCL/P risk (rs17820943: C vs T: OR = 0.76, 95% CI = 0.70-0.82; CC vs CT: OR = 0.75, 95% CI = 0.67-0.85; CC vs TT: OR = 0.58, 95% CI = 0.49-0.67; CC + CT vs TT: OR = 0.67, 95% CI = 0.59-0.77; CT + TT vs CC: OR = 1.43, 95% CI = 1.28-1.60; rs6072081: A vs G: OR = 0.77, 95%CI = 0.68-0.86; AA vs AG: OR = 0.76, 95%CI = 0.64-0.90; AA vs GG: OR = 0.58, 95%CI = 0.45-0.74; AA + AG vs GG: OR = 0.68, 95%CI = 0.54-0.84; AG + GG vs AA: OR = 1.40, 95% CI = 1.19-1.65). The results of the present meta-analysis indicate that in an East Asian population, for both rs17820943 and rs6072081 were associated with NSCL/P.